Is PTSD symptomatology a mechanism of emotional regulation? Insights from an interdisciplinary point of view - Rojas-Saffie, Juan Pablo; Álamos-Vial, Nicolás; Pinzón-Merchán, Manuela (Frontiers in Psychology, 2025)
Post-traumatic stress disorder (PTSD) symptomatology has historically been considered a psychic ailment that is part of a mental disorder. However, it has often been proposed that it could play an adaptive role, in that it would prevent individuals from being exposed to content or situations that they would not be prepared to process. Within the literature on emotional regulation (ER), PTSD symptomatology has commonly been linked to the concept of emotional dysregulation (ED). However, some definitions open the possibility that traumatic symptomatology could be considered ER, from which delicate conclusions would follow. To resolve this dilemma, we turn to interdisciplinary dialogue, specifically with the aid of Thomistic anthropology, whose concepts allow us to understand precisely the relationship between voluntary and involuntary processes and the close relationship between the concepts of reason and regulation. Even though part of the PTSD symptomatology involves psychic mechanisms aimed at modifying emotional states, it is concluded that it is necessary to continue conceptualizing it as ED. The theoretical and practical implications of this discussion are reviewed.